Brand Love as a Key Mediator: Linking Product and Web Design Quality to Purchase Decisions among Shopee Consumers in West Kalimantan - Cristianto, Dwi Adnes Julians; Hiong, Lauw Sun; Siam, Stivenes Tjin (Dinasti International Journal of Economics, Finance & Accounting, 2026)
The rapid growth of e-commerce in Indonesia has significantly transformed consumer shopping behavior and intensified competition among digital platforms. This study aims to examine the influence of product quality and website design quality on purchase decisions, as well as to analyze the mediating role of brand love among Shopee users in West Kalimantan. A quantitative approach was employed using a survey method involving 200 respondents across several regions in West Kalimantan. Data were analyzed using Structural Equation Modeling with AMOS, and the mediating effect was tested using the Sobel test. The results indicate that product quality and website design quality have a positive and significant effect on purchase decisions. Both variables also significantly influence brand love, which in turn has a positive and significant effect on purchase decisions. Furthermore, brand love is proven to significantly mediate the relationship between product quality and website design quality on purchase decisions. These findings highlight the important role of emotional factors in strengthening the influence of quality attributes on consumer purchase decisions in the e-commerce context. This study contributes to the development of digital marketing literature and provides practical implications for businesses to develop strategies that emphasize both quality and emotional consumer engagement.